Molecular Cloning of Pigeon UDP-galactose:β-d-Galactoside α1,4-Galactosyltransferase and UDP-galactose:β-d-Galactoside β1,4-Galactosyltransferase, Two Novel Enzymes Catalyzing the Formation of Galα1–4Galβ1–4Galβ1–4GlcNAc Sequence - Suzuki, Noriko (American Society for Biochemistry and Molecular Biology, 2010)
We previously found that pigeon IgG possesses unique N-glycan structures that contain the Galα1–4Galβ1–4Galβ1–4GlcNAc sequence at their nonreducing termini. This sequence is most likely produced by putative α1,4- and β1,4-galactosyltransferases (GalTs), which are responsible for the biosynthesis of the Galα1–4Gal and Galβ1–4Gal sequences on the N-glycans, respectively. Because no such glycan structures have been found in mammalian glycoproteins, the biosynthetic enzymes that produce these glycans are likely to have distinct substrate specificities from the known mammalian GalTs. To study these enzymes, we cloned the pigeon liver cDNAs encoding α4GalT and β4GalT by expression cloning and characterized these enzymes using the recombinant proteins. The deduced amino acid sequence of pigeon α4GalT has 58.2% identity to human α4GalT and 68.0 and 66.6% identity to putative α4GalTs from chicken and zebra finch, respectively. Unlike human and putative chicken α4GalTs, which possess globotriosylceramide synthase activity, pigeon α4GalT preferred to catalyze formation of the Galα1–4Gal sequence on glycoproteins. In contrast, the sequence of pigeon β4GalT revealed a type II transmembrane protein consisting of 438 amino acid residues, with no significant homology to the glycosyltransferases so far identified from mammals and chicken. However, hypothetical proteins from zebra finch (78.8% identity), frogs (58.9–60.4%), zebrafish (37.1–43.0%), and spotted green pufferfish (43.3%) were similar to pigeon β4GalT, suggesting that the pigeon β4GalT gene was inherited from the common ancestors of these vertebrates. The sequence analysis revealed that pigeon β4GalT and its homologs form a new family of glycosyltransferases.